Direct and indirect determination of electrocaloric effect in Na0.5Bi0.5TiO3 - Birks, Eriks; Dunce, Marija; Peräntie, J.; Hagberg, J.; Sternberg, Andris (AIP Publishing, 2017)
Direct and indirect studies of the electrocaloric effect were carried out in poled and depoled Na0.5Bi0.5TiO3. For this purpose, polarization and electrocaloric effect temperature change measurements were made at different electric field pulses as a function of temperature. The applicability of the widely used indirect electrocaloric effect determination method, using the Maxwell relation, was critically analyzed with respect to the reliable direct measurements. Quantitative differences were observed between the results obtained by both approaches in the case of the poled Na0.5Bi0.5TiO3 sample. These differences can be explained by the temperature-dependent concentration of domains oriented in the direction of the applied electric field. Whereas in depoled Na0.5Bi0.5TiO3, which is characterized by the electric field dependence of polar nanoregions embedded in a nonpolar matrix, the Maxwell relation is not applicable at all, as it is indicated by the obtained results. Possible mechanisms which could be responsible for the electrocaloric effect in the relaxor state were considered. The results of this study are used to evaluate the numerous results obtained and published by other authors, using the Maxwell relation to indirectly determine the electrocaloric effect. The reason for the negative values of the electrocaloric effect, obtained in such a way and widely discussed in the literature in the case of Na0.5Bi0.5TiO3, has been explained in this study.
This work has been supported by the National Research Program in the framework of the project “Multifunctional Materials and composites, photonics and nanotechnology (IMIS2).”
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics